Fundamental study of multi-track friction surfacing deposits for dissimilar aluminum alloys with application to additive manufacturing. (July 2022) - Soujon, Malte; Kallien, Zina; Roos, Arne; Zeller-Plumhoff, Berit; Klusemann, Benjamin
Graphical abstract: Highlights: Overlap and behavior on edges are investigated for multi-track friction surfacing. Defect volume distribution is extensively studied via micro computed tomography. Post-processing via hybrid friction diffusion bonding consolidated defects. Defect-free structure underlines feasibility as solid state AM techology. Abstract: Friction surfacing is an emerging solid-state coating technology based on frictional heat induced plastic deformation at the tip of a consumable metallic stud that allows to deposit layers with a fine-grained recrystallized microstructure at temperatures below the melting point. The generation of sound, defect-free metallurgical joints between multiple adjacent overlapping friction surfacing deposits, also referred to as multi-track friction surfacing, from dissimilar aluminum alloys is the focus of this experimental work. An extensive volumetric defect analysis is carried out for various overlap configurations, including post-processing strategies in order to assess the inter-track bonding integrity using microscopic characterization techniques and micro-computed tomography. The effect of layer arrangement and overlap distance on the volumetric defect formation in both inter-track and layer-to-substrate interface is quantified and discussed. Post-processing via hybrid friction diffusion bonding process demonstrates a significant reduction in defect volume ratio, proving higher material efficiency. The gained knowledge was used to successfully build a multi-track multi-layer friction surfacing stack, demonstrating the suitability of this process for large-scale additive manufacturing components. The subsequent mechanical analysis reveals excellent homogeneous isotropic tensile properties of the additive structure in the range of the base material tensile strength.